Exploring the role of surface modifications of TiNi-based alloys in evaluating in vitro cytocompatibility: a comparative study. (21st October 2020) - Kokorev, Oleg; Chekalkin, Timofey; Marchenko, Ekaterina; Yasenchuk, Yuri; Gunther, Sergey; Serebrov, Vladimir; Chernyshova, Alena; Obrosov, Aleksei; Uludintceva, Elena; Kang, Ji-Hoon
Abstract: The aim of this study was the comparative analysis of in vitro bio-testing of solid and porous TiNi samples with modified surfaces (intact, oxidated, and etched). Tests for cytocompatibility, hemolysis, and cytotoxicity (MTT) as well as visualization by confocal and scanning electron microscopy have shown that the chemically modified samples are the most cytocompatible. The intact and etched samples did not induce hemolysis greater than 2%, and thus they comply with the ISO 10993-4:2018 standard for hemolysis by blood-contacting biomaterials. Direct culture of etched samples with MCF-7 cells and human leukocytes showed low cytotoxicity. At the same time, the cytotoxicity of samples oxidated at 500 °C was significantly greater than that of the etched samples. Confocal and electron microscopy also confirmed the abovementioned quantitative data. The cells attached to the etched surface in numbers sufficient for them to be able to grow and proliferate on this substrate in vitro . These findings indicate that solid and porous TiNi alloy with surface modifications achieved by a cost-effective method is biotolerable and promising for clinical use and for tissue engineering.